An online course about cosmetics improves skin care practices and skin health - Li, Yu; Hua, Wei; Tang, Jie; Xiong, Lidan; Li, Li (Frontiers in Public Health, 2022)
Background: The incidence of cosmetics-associated dermatoses is on the rise recently while the awareness and knowledge about proper utilization of cosmetics are insufficient in both the public and specialists due to limited education about cosmetics. Methods: Our aim was to build and enhance the public’s ability to select appropriate cosmetics, manage possible dermatoses and improve skin-care practices and skin health by offering access to medical information via free online courses. Consequently, we launched a massive open online course (MOOC), Appreciation and Analysis of Cosmetics. An online questionnaire was also sent to evaluate the effectiveness of the course. Results: Nearly 540,000 learners were enrolled in the course since 2014. In the discussion forum, there were 8383 posts and 73014 replies in total, where learners were mostly concerned about topics of sun protection, cleansing and proper utilization of cosmetics in some skin diseases. 645 learners answered the questionnaire with 88.84% of the them changed skin care practices and 50.39% reported improvement in skin health. Moreover, participants who completed the course reported better understanding and utilization of cosmetics-related knowledge (P values < 0.05). 72.09% of respondents were willing to recommend this course to others. Conclusions: Free online public courses are feasible for conducting public health education campaigns related to cosmetics and associated dermatology to lower the incidence of cosmetics-associated dermatoses.